Dynamique des savoirs et des échanges d’un produit de collecte en territoire transfrontalier - Laval Pauline (Confins)
Açai palm (Euterpe oleracea Mart.), also called wassaï or pinot in French Guyana, is native from the Amazon Basin in South America. From its fruits, indigenous people are used to prepare a thick juice, which is a staple food during the period of fruiting of the palm tree. This juice is henceforth fashionable in urban zones in Brazil, and is exported under a wide range of industrial products, thanks to its recognized energy and anti-oxidizing properties. If the major part of the production and the transformation of açai takes place in Belém, in the State of Pará in Brazil, many other production sites exist on a smaller scale, because the fruit as the nectar, highly perishable, cannot be transported. In this paper we focus on the production chain of açai juice in the lower Oyapock region, which is the river border between French Guiana and Amapá, a State of Brazil. In the theoretical framework of ethnoecology, we study the impacts of the border on the dynamics of knowledge and exchanges of açai. More than hundred semi-directive interviews were conducted among different ethnic groups of low Oyapock, as well as works of participating observation, of mapping of the growth areas of açai palm, and a trilingual specialized lexicon was made. The results reveal a great diversity of knowledge, know-how and uses of this palm tree among the nine ethnic groups living in the region. These are mostly specific to each group, and in loss of speed, safe concerning the consumption of nectar, which is common to all the ethnic groups and is increasing. The knowledge and skills dedicated to palm domestication and to the preparation of the nectar are clarified. With the aim of understanding the distribution of the palm tree on this territory, the mapping of the zones of growth of the palm tree in the region is established by taking into account three main ecosystems distinguished by indigenous people, as well as the zones of collection and circuits followed by fruits and juice throughout the process of production and consumption. The final discussion approaches the problem of tenure of lands on each bank of the river Oyapock. The situation is blocked and that hinders the conditions of collection fruits, and slows down the improvement of collected volumes. Finally, we question the impact of the construction of a bridge on the Oyapock river, on the organization of the actors of the network.